Chemical Composition of Essential Oil of Bauhinia acuminata Leaves - Vasudevan, Vipinlal; Mathew, Joseph; Baby, Sabulal (Asian Journal of Chemistry, 2012)
Essential oil isolated by hydrodistillation of the fresh leaves of Bauhinia acuminata was analyzed by GC-MS. Nineteen compounds comprising 89.9 % of the leaf oil were identified. The leaf oil was characterized by absence of monoterpenioids. Phytol (65.90 %) was identified as major constituent in B. acuminata leaf oil. Sesquiterpenoids, b-caroyphyllene (13.87 %) and caryophyllene oxide (3.15 %), were the other major constituents.